2009
DOI: 10.1111/j.1476-5381.2009.00360.x
|View full text |Cite
|
Sign up to set email alerts
|

Induced translocation of glycosylphosphatidylinositol‐anchored proteins from lipid droplets to adiposomes in rat adipocytes

Abstract: Background and purpose: Adipocytes release membrane vesicles called adiposomes, which harbor the glycosylphosphatidylinositol-anchored proteins (GPI proteins), Gce1 and CD73, after induction with palmitate, H2O2 and the sulphonylurea drug glimepiride. The role of lipid droplets (LD) in trafficking of GPI proteins from detergent-insoluble, glycolipid-enriched, plasma membrane microdomains (DIGs) to adiposomes in rat adipocytes was studied. Experimental approach: Redistribution of Gce1 and CD73 was followed by p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 71 publications
1
38
0
Order By: Relevance
“…Previous studies have identified exosomes in the culture supernatant of mouse adipose tissues (Deng et al, 2009), rat primary adipocytes (Müller et al, 2009a;Müller et al, 2009b;Müller et al, 2011), and mouse adipocyte cell line 3T3-L1 (Ogawa et al, 2010;Sano et al, 2014). Deng et al (2009) to lipogenesis and promote lipid accumulation in recipient 3T3-L1 adipocytes (Sano et al, 2014).…”
Section: Aim Of Studymentioning
confidence: 99%
“…Previous studies have identified exosomes in the culture supernatant of mouse adipose tissues (Deng et al, 2009), rat primary adipocytes (Müller et al, 2009a;Müller et al, 2009b;Müller et al, 2011), and mouse adipocyte cell line 3T3-L1 (Ogawa et al, 2010;Sano et al, 2014). Deng et al (2009) to lipogenesis and promote lipid accumulation in recipient 3T3-L1 adipocytes (Sano et al, 2014).…”
Section: Aim Of Studymentioning
confidence: 99%
“…Published procedures were used for the preparation of LD and DIGs (from 2.5 × 10 6 cells per incubation; Müller et al, 2002;2008a, d), determination of 5′-nucleotidase activity (Müller et al, 2008d), isoproterenol-induced lipolysis with enzymic determination of the glycerol released (with 1.0 × 10 6 cells in 1 ml of incubation volume; Müller et al, 2003), fatty acid esterification as the incorporation of [1-14 C]palmitate into total acylglycerols (Müller et al, in press), protein concentration using the BCA method (Pierce) with BSA as calibration standard and PC content of ADIP (Müller et al, 2009a), sodium dodecylsulphate polyacrylamide gel electrophoresis (SDS-PAGE; 4-12% Bis-TRIS precast gel, pH 6.4, 4-morpholineethanesulfonic acid [MES]-SDS running buffer) under reducing conditions (Müller et al, 2008a), extraction and precipitation of proteins from LD, DIGs and incubation medium under native conditions (Müller et al, 2009b) and treatment of ADIP, DIGs, LD or incubation medium with alkaline Na 2 CO 3 , NaCl, detergents, free and cholesterol-bound methylβ-cyclodextrin (m-βCD), (glycosyl)phosphatidylinositol-specific phospholipase C (G)PI-PLC from Bacillus cereus or NaNO 2 (0.25 M, adjusted with sodium acetate to pH 4.0, 3 h at 25°C) (Müller et al, 1997b(Müller et al, , 2002(Müller et al, , 2009a. Concentration-response curves were fitted using the GraphPad Prism 4.03 software (GraphPad Software Inc., La Jolla, CA, USA).…”
Section: Miscellaneousmentioning
confidence: 99%
“…The GPI anchor of Gce1 and CD73 becomes embedded in the extracellular leaflet of the adiposomal phospholipid bilayer and the protein moieties exposed at the adiposomal surface [139,140] . These adiposomes resemble the well-characterized microvesicles and exosomes harbouring subsets of transmembrane [141][142][143] and GPI proteins [82,139,144] , which are released from most mammalian cells into the circulation in vivo or into the incubation medium in vitro. The release of microvesicles following plasma membrane blebbing or shedding as well as of exosomes following plasma membrane fusion, that is exocytosis, of so-called multivesicular bodies, which both presumably occur at plasma membrane DIGs [142][143][144][145][146][147][148][149][150][151][152][153][154][155][156] , is either constitutive [145] or upregulated by cellular activation or apoptosis [146][147][148] .…”
Section: Trafficking Of Gpi Proteins Between Adipocytesmentioning
confidence: 99%